Motor Imagery Experiences and Use: Asking Patients after Stroke Where, When, What, Why, and How They Use Imagery: A Qualitative Investigation. (22nd April 2012) - Schuster, Corina; Glässel, Andrea; Scheidhauer, Anne; Ettlin, Thierry; Butler, Jenny
Abstract : Background . A framework on where, when, what, why, and how to use imagery from sports psychology was explored whether it can be applied in patients after stroke in their chronic stage. Methods . Eleven patients (ages 31–85, 3 females, 1.3–6.4 years after stroke) were interviewed. Semistructured interviews were conducted before and after a two-week MI intervention period with six MI sessions. Information was obtained regarding experiences and knowledge of MI, and the evaluation of an MI practical example. The coding scheme was based on the framework and a hierarchical categorisation. Results . Information regarding domains where, when, what, why, and how to use imagery was addressed. Patients imagined themselves as healthy individuals, did not focus on surroundings during MI practice, and reported to use positive imagery only. After MI training, patients became more flexible regarding their location and position during MI practice. Conclusions . MI became an automatic process, and patients did not need specific concentration and quietness as mentioned in the first interview. Patients recommended daily MI training and began to transfer MI to practice movements that were affected by the stroke. In contrast to sports, patients did not talk about how MI was triggered rather than how MI was designed.